Revisiting radial forearm free flap for successful venous drainage - Yong Hoon Cha; Woong Nam; In-Ho Cha; Hyung Jun Kim (SpringerOpen, 2017)
Abstract Tissue defect reconstruction using radial forearm free flap (RFFF) is a common surgical technique whose success or failure is mainly dependent on venous drainage. RFFF has two major venous outflow systems, superficial and deep vein. Drainage methods include combining both systems or using one alone. This review aims to recapitulate the vascular anatomy and network of RFFF as well as shed light on deep vein as a reliable venous drainage system. We also discuss basic evidence for and advantages of single microanastomosis with coalesced vein to overcome technical difficulties associated with the deep vein system.